Intifadah al-Qahirah fi 17, 18 Yanayir 1997, hawadith 19 Yanayir 1977 bi al-Jizah, qadiyyah Hizb al-'Ummal al-Shuyu'i al-Misri, qadiyyah Hizb al-'ummal wa al-Hizb al-Shuyu'i al-Misri amam al-mahkamah al-'askariyyah al-'ulya ([s.n.], 2002)
'The uprising of Cairo on 17, 18 January 1997, the events of 19 January 1977 in Giza, the trial of the Egyptian Communist Workers' Party, the trial of the Workers' Party and the Egyptian Communist Party in the Supreme Military Court' Politics.